2011
DOI: 10.1111/j.1750-3841.2011.02356.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Chinese Vinegars Based on Headspace Solid‐Phase Microextraction‐Gas Chromatography Mass Spectrometry of Volatile Compounds and Multivariate Analysis

Abstract: Headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography mass spectrometry (GC-MS) was applied for the determination of the characteristic volatile profiles of Chinese vinegars. Multivariate statistical techniques, such as principal component analysis (PCA) and cluster analysis (CA), were used to characterize the different Chinese vinegars by types, fermentation method, and production area. A total of 56 volatile compounds were identified, including 15 esters, 10 aldehydes, 5 acids, 12 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 40 publications
(46 reference statements)
2
88
0
Order By: Relevance
“…This result is similar to a previous study, which proposed semi-quantitative result of furfural ranged from 21 to 27 mgL −1 (Xiao et al 2011). In addition, our study identified and quantified 2-Furyl methyl ketone, which was first found in vinegar.…”
Section: Volatile Profile Of Vinegar Samplessupporting
confidence: 80%
See 3 more Smart Citations
“…This result is similar to a previous study, which proposed semi-quantitative result of furfural ranged from 21 to 27 mgL −1 (Xiao et al 2011). In addition, our study identified and quantified 2-Furyl methyl ketone, which was first found in vinegar.…”
Section: Volatile Profile Of Vinegar Samplessupporting
confidence: 80%
“…H e t e r o c y c l i c c o m p o u n d s , s u c h a s f u r f u r a l , tetramethylpyrazine, trimethylpyrazine and furfural alcohol, and phenols were first quantified in SAV in our studies, which were only identified and semi-quantified in the literature (Lu et al 2011;Xiao et al 2011). Among heterocyclic compounds, the concentration of tetramethylpyrazine was the highest, which was 127.13 mgL −1 .…”
Section: Volatile Profile Of Vinegar Samplesmentioning
confidence: 98%
See 2 more Smart Citations
“…The most abundant aldehyde was benzaldehyde, followed by furfural. The TP5 sample group had the highest content of benzaldehyde, which was described as having sweet, fruity, nutty and caramel-like odors (Xiao et al, 2011).…”
Section: Resultsmentioning
confidence: 99%